Efeito da aplicação de lodo de esgoto na severidade da murcha-de-curtobacterium em feijoeiro - Rodrigues, Ronaldo Bueno [UNESP]; Silva Júnior, Tadeu Antônio Fernandes Da [UNESP]; Maringoni, Antonio Carlos [UNESP] (Grupo Paulista de Fitopatologia, 2006)
This work was aimed at evaluating the effect of different sewage sludge concentrations (SS) on the reduction of the severity of curtobacterium wilt in bean plants (Pérola cultivar), and on plant development (dry mass of the above-ground part of plants), in two assays under greenhouse conditions. In the first assay, SS doses of 0, 2.5, 5.0, 7.5, and 10% were used. For the second assay, SS doses were 0, 0.5, 1.0, 1.5, 2.0, and 2.5%, incorporated in soil, with previously corrected pH and added with chemical fertilizers at the rate recommended for the crop. Plants that had not been inoculated with the pathogen were maintained in both assays. No efficacy was verified for the different SS doses studied in the assays on the reduction of disease severity symptoms, as well as on dry mass of inoculated plants. Concentrations of SS incorporated to the substrate higher than 5% were toxic to bean plants, reducing dry mass of plants.

O presente trabalho teve por objetivo avaliar, sob condições de casa de vegetação, o efeito de lodo de esgoto (LE) na redução da severidade de murcha-de-curtobacterium em feijoeiro, cultivar Pérola, e no desenvolvimento das plantas (massa seca da parte aérea). No primeiro ensaio foram empregadas as doses de LE: 0; 2,5; 5,0; 7,5 e 10%, e no segundo ensaio as doses de LE: 0; 0,5; 1,0; 1,5; 2,0 e 2,5% incorporados em solo com pH previamente corrigido e adubado com fertilizantes minerais na dose recomendada para a cultura. Nos dois ensaios foram conduzidas plantas não-inoculadas com o patógeno. Não foi verificado o efeito do lodo na redução da severidade dos sintomas da doença, bem como na massa seca da parte aérea das plantas inoculadas. Concentrações superiores à 5% de LE incorporado ao substrato foram fitotóxicos às plantas de feijoeiro, reduzindo a massa seca da parte aérea.
Effect of sewage sludge application on the severity of curtobacterium wilt in bean plants
Keywords: Curtubacterium flaccumfaciens pv flaccumfaciens; Phaseolus vulgaris; plant disease control; Curtubacterium flaccumfaciens pv flaccumfaciens; Phaseolus vulgaris; controle de doença; matéria orgânica